Volcanoes magnify Metro Manila's southwest monsoon rains and lethal floods - Lagmay, Alfredo Mahar F.; Bagtasa, Gerry; Crisologo, Irene A.; Racoma, Bernard Alan B.; David, Carlos Primo C. (Frontiers in Earth Science, 2015)
Many volcanoes worldwide are located near populated cities that experience monsoon seasons, characterised by shifting winds each year. Because of the severity of flood impact to large populations, it is worthy of investigation in the Philippines and elsewhere to better understand the phenomenon for possible hazard mitigating solutions, if any. During the monsoon season, the change in flow direction of winds brings moist warm air to cross the mountains and volcanoes in western Philippines and cause lift into the atmosphere, which normally leads to heavy rains and floods. Heavy southwest monsoon rains from 18-21 August 2013 flooded Metro Manila (population of 12 million) and its suburbs paralyzing the nation’s capital for an entire week. Called the 2013 Habagat event, it was a repeat of the 2012 Habagat or extreme southwest monsoon weather from 6-9 August, which delivered record rains in the mega city. In both the 2012 and 2013 Habagat events, cyclones, the usual suspects for the delivery of heavy rains, were passing northeast of the Philippine archipelago, respectively, and enhanced the southwest monsoon. Analysis of Doppler data, rainfall measurements, and Weather Research and Forecasting (WRF) model simulations show that two large stratovolcanoes, Natib and Mariveles, across from Manila Bay and approximately 70 km west of Metro Manila, played a substantial role in delivering extreme rains and consequent floods to Metro Manila. The study highlights how volcanoes, with their shape and height create an orographic effect and dispersive tail of rain clouds which constitutes a significant flood hazard to large communities like Metro Manila.